A novel three tier internet of things health monitoring system - Deepika N,; M. Anand; F. Jerald (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Internet of things is a technology where day to day devices, processing, and communication become smarter, intelligent and informative respectively. Health monitoring system is one the most important applications enabled by IOT. IOT health monitoring system comprises of sensors, network and a remote server (cloud). It provides multi-dimensional health monitoring and also suggests treatments. In this paper we have proposed a novel three tier health monitoring system , which stores and process the huge amount of sensor data outside the device using a  technology called  cloud computing. When the observed clinical sensor value exceeds the threshold clinical value, the system sends alert message to the doctor and caretakers. The history of data and observed data is stored in the cloud for a longer time and it can be viewed by logging into the website.